SOCIO-CULTURAL DETERMINANTS SHAPING YOUTH INITIATIVE IN THE CONTEMPORARY SOCIAL SPACE - Abdurakhmonov Khasan Ibrokhimovich (Innovate Conferences, 2025)
This article provides a scientific and analytical examination of the socio-cultural determinants shaping youth initiative in the contemporary social space. The study explores how family, education systems, cultural values, media environments, and civil society institutions influence young people’s social activity, civic engagement, and capacity for initiative. Special attention is given to the impact of globalization and digital culture on youth identity formation and social participation. The article also highlights the role of cultural capital and social capital in fostering sustainable youth initiatives and critically assesses existing institutional mechanisms supporting youth engagement. The findings emphasize the need for an integrated socio-cultural approach to strengthening youth initiative as a key factor in social development.
Keywords: youth initiative, socio-cultural determinants, social activity, cultural environment, civil society, globalization, youth engagement.